The Disruption of a Nuclear Export Signal in the C-Terminus of the Herpes Simplex Virus 1 Determinant of Pathogenicity UL24 Protein Leads to a Syncytial Plaque Phenotype - Carmen Elena Gonzalez; Nawel Ben Abdeljelil; Angela Pearson (Viruses, 2023)
UL24 of herpes simplex virus 1 (HSV-1) has been shown to be a determinant of pathogenesis in mouse models of infection. The N-terminus of UL24 localizes to the nucleus and drives the redistribution of nucleolin and B23. In contrast, when expressed alone, the C-terminal domain of UL24 accumulates in the Golgi apparatus; its importance during infection is unknown. We generated a series of mammalian expression vectors encoding UL24 with nested deletions in the C-terminal domain. Interestingly, enhanced nuclear staining was observed for several UL24-deleted forms in transient transfection assays. The substitution of a threonine phosphorylation site had no effect on UL24 localization or viral titers in cell culture. In contrast, mutations targeting a predicted nuclear export signal (NES) significantly enhanced nuclear localization, indicating that UL24 is able to shuttle between the nucleus and the cytoplasm. Recombinant viruses that encode UL24-harboring substitutions in the NES led to the accumulation of UL24 in the nucleus. Treatment with the CRM-1-specific inhibitor leptomycin B blocked the nuclear export of UL24 in transfected cells but not in the context of infection. Viruses encoding UL24 with NES mutations resulted in a syncytial phenotype, but viral yield was unaffected. These results are consistent with a role for HSV-1 UL24 in late cytoplasmic events in HSV-1 replication.